Naşterea şi căsătoria la populaţia de romi - Voicu, Mălina; Popescu, Raluca (Calitatea Vieții, 2006)
Poor and often marginalized population, the Roma people continue to have a traditional lifestyle. This fact has affected the family life, too. The previous studies demonstrate that the Roma people prefer to live in large families, to have many children and to get married early in the life. This study aims to investigate the attitudes of the Roma women and girls towards the family formation and to the childbirth. In order to reach our research goals we have conducted some group – discussions in some Roma communities from Tulcea, Brăila, Constanţa and Ialomiţa counties. Another research goal is to compare the model of family formation of the Roma population with the similar model of the majority of population, using quantitative data.